Disruptive education: reversing the value chain - Mishra, Mukti (Henry Stewart Talks, 2016)
Current situation of the education in India, Centurion’s learning iteration process, Centurion’s strategic iteration process in practice, Gram Tarang: Centurion’s social entrepreneurship outreach, Disruptive education: the flower approach